Implementation of Online Learning in The New Normal Era: PAI Teacher Efforts and Strategies - Mohammad Saat Ibnu Waqfin; Istaftihul Unailah Faz (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Education is an effort to prepare students to perform various roles in their environment appropriately in the future. So far, Islamic Religious Education is only considered as a complementary subject and many people consider Islamic Education is not very important. With the learning process of Islamic Religious Education students are also expected to be more internal and appreciate the teachings of Islam. It is interesting to discuss. Educators are required to be able to vary the models in learning so that students are more motivated and able to master the materials provided. The purpose of this study is to know the efforts and strategies of applying online learning in Islamic Religious Education (PAI) courses in the situation of the Covid-19 pandemic and the obstacles contained in the implementation of online learning in Islamic Religious Education (PAI) courses. This research can also be used as an evaluation of the implementation of online learning and preparation materials for the management of online learning in the face of the new normal era.